(untitled) (MAUSAM, 2003)
The onset and withdrawal dates of northeast monsoon over coastal Tamil Nadu have been objectively determined for the ten year period 1991-2000. The statistics of onset and withdrawal dates for the 100 year 20th century period 1901-2000 have been presented and discussed. It has been shown by employing techniques such as harmonic/spectral analysis and cross lag correlation over 100 year rainfall data, that the daily rainfall of coastal Tamil Nadu during September-February displays a prominent 40-days periodicity and that rainfall anomalies move from south to north taking nearly 2 days to traverse between Pamban and Chennai separated latitudinally by nearly 400 km. In 70% of the years the onset and withdrawal process of northeast monsoon gets excited by the 40-day periodicity.